Sound in Daniel Deronda - Michael Hollington (Cahiers Victoriens et Edouardiens)
The aim of this paper is to explore the significance of sounds negative and sounds positive in Daniel Deronda, tracing a sequence of significant sounds from the near-silence of the opening scene in a gaming room to the jubilant licence of sound in the concluding wedding scene. It is particularly interested in a series of shrieks from the heroine, Gwendolen—three in number, at the charade, at the time of her wedding, and at the death of her husband—which mark points at which she recognises the terrible course in life on which she has launched herself. After the third of these, an alternative rhetoric of sound takes over, in which she is launched on a gradual purgatorial process of redemption.